Application of Modified Integral Resonant Control for suppressing stick–slip oscillations in drill-strings. - Zakaria Taibi; Djokhdem, Abdenour; Yousfi, Mohamed Riad (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : GÉNIE DES PROCÉDÉS, 2024)
This thesis addresses the issue of unwanted downhole vibrations that hinder the efficiency of drilling operations, increasing costs and associated risks. The focus is on the "stick-slip" vibrations phenomenon, one of the significant challenges in deep drilling operations. Simulation results demonstrated that applying an MIRC controller can effectively reduce these vibrations and improve the stability of drilling operations. The simulation model illustrates how this controller can be integrated with the drilling system to achieve quick and precise responses to changes in torque, enhancing drilling efficiency and reducing bit wear and equipment failure.
Gas engineering